Strengthen Nerves & Sharpens Skill – Biochemic System of Medicine (Homoeopathy for All, 2022)
Biochemic combinationsor cell salts  or tissue salts have been dispensed  as combination since the time of  Schussler. A German physician Dr.  Schussler realized that a deficiency  of certain tissue salts can lead to  a number of diseases. These salts  are normal components of healthy  tissues are essential for the growth  and development of the body.  Although this system is considered  to be an offshoot of Homoeopathy,  it has its independent standing.  Unlike homeopathic medicines that  are in thousands and are available  in various potencies or scales, the  biochemic remedies are just twelve  in number and are available in  the 3X, 6X, 12X,
Keywords: combinationsor; homeopathic